Profluorescent substrates for the screening of olefin metathesis catalysts - Reuter, Raphael; Ward, Thomas R. (Beilstein Journal of Organic Chemistry, 2015)
Herein we report on a 96-well plate assay based on the fluorescence resulting from the ring-closing metathesis of two profluorophoric substrates. To demonstrate the validity of the approach, four commercially available ruthenium-metathesis catalysts were evaluated in six different solvents. The results from the fluorescent assay agree well with HPLC conversions, validating the usefulness of the approach.
Keywords: fluorescence; microplate screening; ring closing metathesis